Prognostic Role of Specific KRAS Mutations Detected in Aspiration and Liquid Biopsies from Patients with Pancreatic Cancer - Hálková, Tereza; Bunganič, Bohuš; Traboulsi, Eva; Minárik, Marek; Zavoral, Miroslav; Benešová, Lucie (Genes, 2024)
Background/Objectives: Although the overall survival prognosis of patients in advanced stages of pancreatic ductal adenocarcinoma (PDAC) is poor, typically ranging from days to months from diagnosis, there are rare cases of patients remaining in therapy for longer periods of time. Early estimations of survival prognosis would allow rational decisions on complex therapy interventions, including radical surgery and robust systemic therapy regimens. Understandably, there is great interest in finding prognostic markers that can be used for patient stratification. We determined the role of various KRAS mutations in the prognosis of PDAC patients using biopsy samples and circulating tumor DNA. Methods: A total of 118 patients with PDAC, clinically confirmed by endoscopic ultrasound-guided fine-needle aspiration biopsy (EUS-FNB), were included in the study. DNA was extracted from cytological slides following a standard cytology evaluation to ensure adequacy (viability and quantity) and to mark the tumor cell fraction. Circulating tumor DNA (ctDNA) was extracted from plasma samples of 45 patients in stage IV of the disease. KRAS mutations in exons 12 and 13 were detected by denaturing capillary electrophoresis (DCE), revealing a minute presence of mutation-specific heteroduplexes. Kaplan-Meier survival curves were calculated for individual KRAS mutation types. Results:KRAS mutations were detected in 90% of tissue (106/118) and 44% of plasma (20/45) samples. All mutations were localized at exon 2, codon 12, with G12D (GGT > GAT) being the most frequent at 44% (47/106) and 65% (13/20), followed by other types including G12V (GGT > GTT) at 31% (33/106) and 10% (2/20), G12R (GGT > CGT) at 17% (18/106) and 10% (2/20), G12C (GGT/TGT) at 5% (5/106) and 0% (0/20) and G12S (GGT/AGT) at 1% (1/106) and 5% (1/20) in tissue and plasma samples, respectively. Two patients had two mutations simultaneously (G12V + G12S and G12D + G12S) in both types of samples (2%, 2/106 and 10%, 2/20 in tissue and plasma samples, respectively). The median survival of patients with the G12D mutation in tissues was less than half that of other patients (median survival 101 days, 95% CI: 80-600 vs. 228 days, 95% CI: 184-602), with a statistically significant overall difference in survival (p = 0.0080, log-rank test), and furthermore it was less than that of all combined patients with other mutation types (101 days, 95% CI: 80-600 vs. 210 days, 95% CI: 161-602, p = 0.0166). For plasma samples, the survival of patients with this mutation was six times shorter than that of patients without the G12D mutation (27 days, 95% CI: 8-334 vs. 161 days, 95% CI: 107-536, p = 0.0200). In contrast, patients with detected KRAS G12R in the tissue survived nearly twice as long as other patients in the aggregate (286 days, 95% CI: 70-602 vs. 162 days, 95% CI: 122-600, p = 0.0374) or patients with other KRAS mutations (286 days, 95% CI: 70-602 vs. 137 days, 95% CI: 107-600, p = 0.0257). Conclusions: Differentiation of specific KRAS mutations in EUS-FNB and ctDNA (above all, the crucial G12D and G12R) is feasible in routine management of PDAC patients and imperative for assessment of prognosis.
Keywords: Circulating Tumor DNA; duktální karcinom slinivky břišní; liquid biopsy; mutation type; Carcinoma, Pancreatic Ductal; KRAS; Endoscopic Ultrasound-Guided Fine Needle Aspiration; nádory slinivky břišní; Humans; tekutá biopsie; lidé středního věku; Biomarkers, Tumor; biopsie tenkou jehlou pod endosonografickou kontrolou; EUS-FNB; Female; mutace; Aged; dospělí; ctDNA; pancreatic cancer; senioři; lidé; protoonkogenní proteiny p21(ras); Liquid Biopsy; cirkulující nádorová DNA; nádorové biomarkery; Adult; ženské pohlaví; Male; Pancreatic Neoplasms; Middle Aged; Proto-Oncogene Proteins p21(ras); prognóza; Aged, 80 and over; senioři nad 80 let; Mutation; mužské pohlaví; prognosis; Prognosis